Comprehensive CRISPR-Cas9 screen identifies factors which are important for plasmablast development - Pinter, Theresa; Fischer, Maria; Schäfer, Markus; Fellner, Michaela; Jude, Julian; Zuber, Johannes; Busslinger, Meinrad; Wöhner, Miriam (Frontiers in Immunology, 2022)
Plasma cells (PCs) and their progenitors plasmablasts (PBs) are essential for the acute and long-term protection of the host against infections by providing vast levels of highly specific antibodies. Several transcription factors, like Blimp1 and Irf4, are already known to be essential for PC and PB differentiation and survival. We set out to identify additional genes, that are essential for PB development by CRISPR-Cas9 screening of 3,000 genes for the loss of PBs by employing the in vitro-inducible germinal center B cell (iGB) culture system and Rosa26Cas9/+ mice. Identified hits in the screen were Mau2 and Nipbl, which are known to contribute to the loop extrusion function of the cohesin complex. Other examples of promising hits were Taf6, Stat3, Ppp6c and Pgs1. We thus provide a new set of genes, which are important for PB development.